Descriptive Analysis of the Patients with Post COVID Interstitial Lung Diseases in a Tertiary Care Hospital in Central Sri Lanka: An Observational Study - Madegedara, Dushantha; Basnayake, Lihini; Bandara, Damith Nissanka (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
Background: To date, COVID-19 continues to remain at pandemic proportions. As of March 2022, COVID-19 has caused over 433 million infections and over 5.9 million deaths around the world. Long COVID associated complications were reported worldwide. COVID associated interstitial lung disease is a well-known, recognized long term consequence. Methodology: A single centre observational study was carried out in the Respiratory Disease Treatment Unit two at National Hospital Kandy, Sri Lanka. Information regarding Demographic, clinical, biochemical and radio graphical characteristics were extracted from the medical records. An interviewer-administered questionnaire was used. Statistical analysis was performed using IBM SPSS statistics data editor. Results: A total of 53 (13.6%) COVID-19 related ILD cases were analysed. Out of them, 38 (71.7%) were males. The median age was 59 years. The majority of patients (81.1%) were given a history of at least one underlying comorbid disease, while Diabetes Mellitus was the commonest (58.4%). Out of the male patients, 17 (47.3%) had a positive smoking history of varying pack years. Different pathological patterns, geographical and zonal distributions, occasionally asymmetrical patterns were observed in HRCT of patients with COVID-19 related ILD. Conclusion: The majority of the COVID-19 related ILD patients were males with multiple comorbidities and had a positive smoking history. The progression of the disease is well displayed in the findings of HRCT. Detection of these findings should alert the clinicians to provide prompt and optimized care in order to minimize the morbidity and mortality of COVID-19 related ILD.